Evaluation of the Combined Effects of Tobacco and Diabetes on Periodontal Health Outcomes in India: A Longitudinal Cohort Study - Anuj Singh Parihar; Jay T. Patel; Ameer A. A. Shaik; Niva Mahapatra; Pradeep Adatrow; Rashmi Laddha; Miral Mehta (Journal of Pharmacy and Bioallied Sciences)
Background: Recognized as a major dental issue, periodontal disease is a dental health challenge that requires due attention due to its dire health consequences. Periodontitis has two notable risk factors: smoking and diabetes; however, there is an evident gap in existing studies in understanding their combined effect on the periodontal health of the Indian population. This longitudinal study investigates the independent and interactive effects of tobacco and diabetes on periodontal health in an Indian cohort. Methods: A representative sample of 800 adults, aged 30–60 years participated in this study. Baseline data were collected through clinical examinations (including periodontal probing depths, clinical attachment loss, bleeding on probing), structured interviews (assessing tobacco use habits and medical history), and blood tests (for HbA1c levels to determine diabetic status). Follow-up assessments were conducted at one-year intervals for a period of five years. Data were analyzed using SPSS to perform regression analyses to assess the associations between tobacco use, diabetes, and periodontal health outcomes, adjusting for potential confounders, such as age, gender, socioeconomic status, and oral hygiene practices. Results: The prevalence of tobacco use in the study population was 35%, while 15% of participants had diabetes. Both tobacco use and diabetes were independently associated with increased risk of periodontitis (OR = 2.5 for tobacco users, 95% CI: 1.8–3.4; OR = 3.1 for diabetics, 95% CI: 2.1–4.5). Individuals with both tobacco use and diabetes exhibited significantly worse periodontal health outcomes compared to those with neither risk factor (OR = 4.8, 95% CI: 3.2–7.2). Conclusions: This study highlights the detrimental impact of tobacco use and diabetes on periodontal health in India.